The Relationship of DPT Immunization, Maternal Education, and Residential Density with ARI Incidence in Toddlers - Putri, Rina Ayu; Lubis, Rahayu (Transpublika Publisher, 2025)
Acute Respiratory Infection (ARI) is a common contagious illness that impacts the respiratory system. The World Health Organization (WHO) reports that ARI is a major contributor to mortality in young children, with a death rate of 15 percent among those under five years old. According to Indonesian Health Survey (SKI) in 2023, incidence rate of ARI in Indonesia is 23.5 percent, with 34.5 percent in toddlers, and in North Sumatra in 2023 is 16.1 percent. The study discusses about the relationship of DPT (Diphtheria, Pertussis, Tetanus) immunization, mother's education and residential density with incidence of ARI on toddlers at Simpang Limun Public Health Center in 2025. The research conducted is an evaluative examination utilizing a cross-sectional approach, involving 101 participants chosen through random selection. The information collected was assessed utilizing the Chi-square test with a 95 percent confidence level (α = 0.05). The results of the bivariate analysis indicated a significant relationship between mother’s education (p = 0.006), DPT immunization (p = 0.001), frequency of DPT immunization (p = <0.001), exclusive breastfeeding (p = 0.006), residential density (p = <0.001), and the presence of smokers in the household (p = 0.022) with the incidence of ARI on toddlers at Simpang Limun Public Health Center in 2025. It is recommended that the staff at Simpang Limun Public Health Center provide education on the importance of primary and booster immunizations for toddlers, exclusive breastfeeding, home health, and the dangers of exposure to cigarette smoke on toddler health.